Morphological Evolution and Extinction of Eodiscids and Agnostoid Arthropods - Huarui Li; Tao Dai; Yanlong Chen; Chunling Xue; Luke C. Strotz (Life)
The temporal range of eodiscids and agnostoid arthropods overlaps with several early Paleozoic geological events of evolutionary significance. However, the responses of agnostids to these events and how the perturbations associated with them (both abiotic and/or biotic) may have impacted agnostids remain uncertain. To address this uncertainty, we employ geometric morphometrics to reconstruct morphospace occupation for agnostids, thereby elucidating their evolutionary response to geological events during the early Paleozoic. The results indicate that maximum morphospace occupation was reached by Cambrian Series 2 and then declined soon thereafter. Subsequent reductions in agnostid morphospace occupation coincide not only with significant abiotic changes and associated extinction events, such as the Botoman–Toyonian Extinctions (BTEs), the Redlichiid–Olenellid Extinction Carbon Isotope Excursion (ROECE), the Drumian Carbon Isotope Excursion (DICE), and the Steptoean Positive Carbon Isotope Excursion event (SPICE), but also with major evolutionary episodes, such as the Great Ordovician Biodiversification Event (GOBE). These repeated and periodic declines in agnostid morphological diversity following Cambrian Series 2 suggest that the extinction of agnostids reflects the culmination of an episodic reduction in morphological occupancy for agnostids rather than a singular, sudden event. Accordingly, it cannot be tied to a single cause, either abiotic or biotic.